A political economy of the Poor People's Campaign: From MLK and Polanyi to Trump. (2nd October 2019) - Callebert, Ralph; Soni, Raji Singh
ABSTRACT: A stalemate has emerged in mainstream liberal/left responses to Trump. Many commentators prefer to see our predicament in terms of either class-based or identity politics. Vis-à-vis the influence of the Chicago school of economics and its structural adjustment schemes, we crosshatch MLK's Poor People's Campaign and Polanyi's Great Transformation to envision overcoming this stalemate. King's effort to radicalize the welfare state from below by linking struggles against poverty, racism, and imperialism shares Polanyi's focus on the economy's embeddedness in society. We underscore the importance of King's and Polanyi's visions for building a leftist coalition that does not divorce social from economic justice.